MicroRNA changes in maternal serum from pregnancies complicated by twin‐twin transfusion syndrome: A discovery study. (18th June 2019) - Mackie, Fiona L.; Baker, Bernadette C.; Beggs, Andrew D.; Stodolna, Agata; Morris, Rachel Katie; Kilby, Mark D.
Abstract: Objective: MicroRNAs (miRNAs) are used as biomarkers in cardiovascular disease and cancer. miRNAs are involved in placental development but have not previously been investigated in twin‐twin transfusion syndrome (TTTS). Our aim is to explore the miRNA profile of TTTS pregnancies. Method: Initial miRNA profiling was performed using a reverse transcription polymerase chain reaction (RT‐PCR) panel on maternal serum samples taken from five women prior to fetoscopic laser ablation for TTTS and compared with serum samples from five women with uncomplicated monochorionic diamniotic twin pregnancies. Validation RT‐PCR was performed in an additional cohort of eight TTTS pregnancies and eight uncomplicated pregnancies. Results: Median gestational age at sampling in the TTTS and control groups was 20 +0  weeks (interquartile range [IQR], 19 +4 ‐20 +0 ) and 20 +2  weeks (IQR, 20 +0 ‐20 +2 ), respectively. All samples passed quality control. One control sample was excluded as a biological outlier. Thirty‐one of 752 miRNAs were significantly different: 17 were upregulated and 14 downregulated in the TTTS group, although they did not remain significant following Benjamini‐Hochberg correction for multiple testing. The six miRNAs chosen for validation demonstrated no significant difference. Conclusion: This is the first study to investigate miRNA changes in TTTS pregnancies. We did not demonstrate a statistically significant difference in miRNAs in TTTS pregnancies, but further investigation is required.